EVALUATING THE IMPACT OF FORENSIC LINGUISTICS EDUCATION ON STUDENT AWARENESS OF LEGAL AND ETHICAL ONLINE BEHAVIOR: - Firdaus, Ahmad Yusuf; Inayati, Nina; Lailiyah, Sufil (International Journal of Community Service in Language, Literature, Culture, and Their Teaching, 2024)
This study evaluates the effectiveness of the community service conducted at SMP Cendikia Insani on the introduction of forensic linguistics. The primary aim of this activity was to enhance students' understanding of language analysis in legal contexts, social media language ethics, and the legal consequences of unethical online behavior. Through materials covering fundamental forensic linguistics concepts, discussions on language ethics, and explanations of the Information and Electronic Transactions Law (UU ITE), students were introduced to essential principles of responsible and ethical communication. Interactive learning methods, including quizzes and case studies, were employed to encourage active student participation and deepen their understanding. The results indicate that students showed increased awareness and understanding of language ethics and the legal implications of online behavior. The high level of enthusiasm during Q&A sessions and discussions reflects the relevance and value of the content delivered. Support from Universitas Abdurachman Saleh Situbondo was crucial to the success of this initiative, reaffirming the shared commitment to holistic and relevant education for the digital generation.